Anion Exchange Membrane Water Electrolysis: High‐Efficiency Anion‐Exchange Membrane Water Electrolyzer Enabled by Ternary Layered Double Hydroxide Anode (Small 28/2021). Issue 28 (15th July 2021) - Lee, Jooyoung; Jung, Hyeonjung; Park, Yoo Sei; Woo, Seongwon; Yang, Juchan; Jang, Myeong Je; Jeong, Jaehoon; Kwon, Nayoung; Lim, Byungkwon; Han, Jeong Woo; Choi, Sung Mook
Abstract : In article number 2100639, Byungkwon Lim, Jeong Woo Han, Sung Mook Choi, and co‐workers present a ternary layered double hydroxide electrode that can be used as the anode of an anion exchange membrane water electrolyzer. This directly grown electrode shows that it can stably produce high‐efficiency and high‐purity hydrogen due to its excellent catalytic properties.